2012
DOI: 10.1007/978-3-642-35623-0_15
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Modelling Complex Workflow Requirements in Web Applications

Abstract: Abstract. Workflow plays a major role in nowadays business and therefore its requirement elicitation must be accurate and clear for achieving the solution closest to business's needs. Due to Web applications popularity, the Web is becoming the standard platform for implementing business workflows. In this context, Web applications and their workflows must be adapted to market demands in such a way that time and effort are minimize. As they get more popular, they must give support to different functional requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…(1) Methods used to deal with internal inconsistency As discussed above, the requirements in context-aware systems are from diverse sources and in diverse formats, and this may lead to internal inconsistency in requirement models. Logical-based methods are suitable for solving this kind of challenge, because they can represent requirements and their related context constraints in logical expressions and use automated analysis tools to detect and resolve the inconsistencies based on predefined logical rules [88], [89].…”
Section: Methods Used To Address the Challenges Of Inconsistencymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Methods used to deal with internal inconsistency As discussed above, the requirements in context-aware systems are from diverse sources and in diverse formats, and this may lead to internal inconsistency in requirement models. Logical-based methods are suitable for solving this kind of challenge, because they can represent requirements and their related context constraints in logical expressions and use automated analysis tools to detect and resolve the inconsistencies based on predefined logical rules [88], [89].…”
Section: Methods Used To Address the Challenges Of Inconsistencymentioning
confidence: 99%
“…Internal inconsistency: In a context-aware system, not only can the requirements from different stakeholders result in internal inconsistency, but also the requirements related to different contexts can cause internal inconsistency [88], [89]. How to model the inconsistent requirements to facilitate their detection and resolution is a challenging task.…”
Section: Inconsistencymentioning
confidence: 99%
“…Researchers have proposed that the modelling of flexible processes should be based on accepted ideas of work practice rather than on software programming principles (Adams, Edmond, and Ter Hofstede 2003). Activity theory, a powerful paradigm to understand human work practices (Kuutti 1996), is believed to be applicable for the analysis of process dynamics (Adams, Edmond, and Ter Hofstede 2003;Adams et al 2006a;Urbieta et al 2012). Previous research has shown that it is possible to elicit data elements and their relationships through activity theory (Chen et al 2013;Karanasios et al 2013).…”
Section: Modelling Collaborative Process Dynamicsmentioning
confidence: 99%